Is internal thoracic artery resistant to reperfusion injury?: evaluation of the storage of free internal thoracic artery grafts - Veres, Gábor; Schmidt, Harald; Hegedűs, Péter; Korkmaz-İçöz, Sevil; Radovits, Tamás; Loganathan, Sivakkanan; Brlecic, Paige; Li, Shiliang; Karck, Matthias; Szabó, Gábor (The journal of thoracic and cardiovascular surgery, 2018)
The in situ internal thoracic artery (ITA) is recognized as the best conduit for coronary artery bypass surgery. The ITA - if it is used as an in situ graft - has a much higher late patency rate than any other arterial graft, including a free ITA graft. We sought to determine if the use of the ITA as an in situ/free graft and its storage in preservation solutions, have an effect on endothelial function.